Porous microcrystalline graphite negative electrode material and preparation method and application thereof
Through vacuum pressure immersion concentration poor alkali activation technology, the problem of uneven distribution of pore structures within graphite particles is solved, the fast charging performance and cycle life of the negative electrode material of lithium-ion battery is improved, and the rapid transmission of lithium ions and material stability is achieved.
Patent Information
- Application Number
- CN202411500300.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing alkali activation technology is difficult to evenly distribute the pore structure inside the graphite particles, resulting in the challenge of insufficient fast charging performance of the negative electrode material of lithium-ion battery and the challenge of not reducing the material cycle life.
The alkali activation method of vacuum pressure impregnation concentration is used to perform multiple treatments on microcrystalline graphite, gradually reduce the alkali solution concentration and increase the pressure, ensure that the alkali solution enters the inside of the particles, forming a deep pore structure, and at the same time, the pore formation and stability are promoted through high-temperature calcination. Particle structure.
The charge and discharge rate performance of porous microcrystalline graphite negative electrode material is significantly improved, while ensuring that the material's cycle life is not reduced. The pore structure is conducive to the rapid transmission of lithium ions.
Smart Images

Figure CN119306216A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials for lithium ion batteries, and in particular, relates to a porous microcrystalline graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in the fields of power, energy storage and consumer electronics due to their high energy density, long cycle life and safety performance. As the most mainstream negative electrode material for lithium-ion batteries, graphite has a theoretical specific capacity of up to 372mAh / g, and has the characteristics of wide range of raw materials, low price and mature technology. However, the rate performance of general graphite negative electrode materials is poor, which makes it difficult to meet the market's fast charging needs. The solutions to improve the fast charging performance of graphite negative electrode materials can be roughly divided into raw material selection, particle size control, microstructure optimization and surface modification. Microstructure optimization such as pore formation has a great influence on performance improvement, and pore formation technologies include alkaline activation, water vapor activation, air activation, carbon dioxide activation, strong oxidant activation, etc. Among these pore formation methods, alkaline activation is widely used because of its controllable pore formation, low equipment requirements and high safety factor. However, the following problems still exist in the use of alkaline activation to form pores in graphite: ① For artificial graphite, due to its good isotropy, the pores generated during the alkali activation process are evenly distributed on the surface. If further etching is carried out, the reaction will still proceed preferentially on the surface and cannot be etched into the interior of the particles; ② For flake graphite, the isotropy is poor, the orientation of the flakes is highly consistent, and the alkali activation occurs preferentially on the end faces of the graphite flakes. During the etching process, the pore structure will extend along the flake direction, and the formed pore structure is easy to collapse; ③ The current alkaline activation technology can only etch within a certain range on the graphite surface, and the internal pore structure of the prepared porous graphite is missing.
[0003] Therefore, during the alkaline activation process, selecting suitable graphite raw materials and uniformly constructing the pore structure on the surface and inside the particles are the keys to achieving porous microcrystalline graphite negative electrode materials, and are also the direction that industry researchers have been working towards for a long time. Summary of the invention
[0004] The main purpose of the present invention is to provide a porous microcrystalline graphite negative electrode material and a preparation method thereof, so as to overcome the deficiencies in the prior art.
[0005] Another object of the present invention is to provide an application of the porous microcrystalline graphite negative electrode material.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: An embodiment of the present invention provides a method for preparing a porous microcrystalline graphite negative electrode material, which comprises: (1) After the microcrystalline graphite is fully contacted with an alkaline solution, it is dried, and then a first calcination is performed in an inert atmosphere to obtain a first porous microcrystalline graphite with grain end faces etched; (2) vacuum pressure impregnating the first porous microcrystalline graphite obtained in step (1) with an alkaline solution, followed by drying, and then performing a second calcination in an inert atmosphere to obtain a second porous microcrystalline graphite with the end faces and the interior of the grains simultaneously etched; Repeat step (2) for more than one time, wherein the concentration of the alkaline solution used in each operation is 5-15% lower than that of the previous operation, and the pressure used in each operation is 10-30% higher than that of the previous operation, to obtain a porous microcrystalline graphite negative electrode material.
[0007] In some embodiments, in step (2), the process conditions adopted for vacuum pressure impregnation include: a vacuum degree of 0.00001 Pa to 100 Pa and a pressure of 1 MPa to 50 MPa.
[0008] An embodiment of the present invention also provides a porous microcrystalline graphite negative electrode material prepared by the aforementioned preparation method, wherein the porous microcrystalline graphite negative electrode material includes aggregates formed by the mutual accumulation of grains with small flake structures, and the porous structure is evenly distributed on the surface and inside of the porous microcrystalline graphite negative electrode material, the porous structure is mainly distributed along the edges of the grains, and the porous structure is located between the grains; wherein the average size of the grains with the small flake structure is below 1 μm, and the true density is 2~2.29 g / cc.
[0009] Furthermore, the porous microcrystalline graphite negative electrode material has a porosity of 5% to 60% and a specific surface area of 1 to 20 m 2 / g.
[0010] The embodiment of the present invention also provides the use of the aforementioned porous microcrystalline graphite negative electrode material in the preparation of a lithium ion battery.
[0011] Correspondingly, an embodiment of the present invention further provides a lithium-ion battery, which includes the aforementioned porous microcrystalline graphite negative electrode material.
[0012] Compared with the prior art, the beneficial effects of the present invention include: 1) The preparation method provided by the present invention selects short-range ordered and long-range disordered microcrystalline graphite as the raw material of the porous graphite negative electrode, and its particles are formed by the accumulation of grains with a grain size of less than 1 μm. The etching action occurs preferentially on the end faces of the graphite sheets during the alkali activation process. During the activation process, the etchant etches along the end faces of different grains toward the inside of the particles, while forming pores inwards and ensuring the structural stability of the particles; 2) The preparation method provided by the present invention repeatedly uses an alkaline solution to perform vacuum pressure impregnation on microcrystalline graphite, so that the alkali can enter the interior of the pore structure, and further etch into the interior of the particles at high temperature, further promoting the formation of the pore structure. At the same time, washing away the alkali on the surface of the microcrystalline graphite can effectively reduce the further etching of the particle surface, which leads to the collapse of the surface structure; 3) The pore structure of the porous microcrystalline graphite negative electrode material prepared by the present invention is conducive to the rapid transmission of lithium ions, significantly improving the charge and discharge rate performance of the material while ensuring that the cycle life of the material is not reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0014] Figure 1 is a morphology image of the porous microcrystalline graphite obtained in step (1) of Example 1 of the present invention; Figure 2 is a morphology diagram of the porous microcrystalline graphite negative electrode material obtained in step (3) of Example 1 of the present invention; Figure 3 This is a morphology diagram of the porous microcrystalline graphite negative electrode material obtained in Comparative Example 2; Figure 4 This is a morphology diagram of the porous microcrystalline graphite negative electrode material obtained in Example 3. DETAILED DESCRIPTION
[0015] In view of the problems existing in the above-mentioned prior art, after long-term research and a large number of experiments, the inventor of this case proposed this technical solution, which mainly provides a method for generating a porous structure on the surface and inside of microcrystalline graphite particles through vacuum pressure impregnation concentration difference alkali activation, aiming to improve the fast charging performance of microcrystalline graphite negative electrode materials while ensuring that the cycle life of the material is not reduced.
[0016] The technical solution, its implementation process and principle will be further explained as follows.
[0017] As one aspect of the technical solution of the present invention, a method for preparing a porous microcrystalline graphite negative electrode material involves: (1) After the microcrystalline graphite is fully contacted with an alkaline solution, it is dried, and then a first calcination is performed in an inert atmosphere to obtain a first porous microcrystalline graphite with grain end faces etched; (2) vacuum pressure impregnating the first porous microcrystalline graphite obtained in step (1) with an alkaline solution, followed by drying, and then performing a second calcination in an inert atmosphere to obtain a second porous microcrystalline graphite with the end faces and the interior of the grains simultaneously etched; Repeat step (2) for more than one time, wherein the concentration of the alkaline solution used in each operation is 5-15% lower than that of the previous operation, and the pressure used in each operation is 10-30% higher than that of the previous operation, to obtain a porous microcrystalline graphite negative electrode material.
[0018] Specifically, if the gradient concentration decreases more slowly, the required pressure will be greater, so that the alkaline solution can be pushed to a deeper part of the particle pore structure, and the pore structure can be formed more effectively during the subsequent heat treatment process. The deeper the pores, the higher the porosity.
[0019] In some specific embodiments, the step (1) comprises: uniformly mixing microcrystalline graphite and an alkaline solution, drying the obtained mixture, introducing an inert gas, heating the mixture to a selected temperature at a heating rate of 1 to 20 °C / min, and performing a first calcination to obtain a first porous microcrystalline graphite with grain end face etching.
[0020] In some specific embodiments, the first porous microcrystalline graphite comprises pores with a size of 10 nm to 1 μm and a depth of 500 nm to 3 μm.
[0021] In some specific embodiments, the microcrystalline graphite used in step (1) includes microcrystalline graphite powder. The present invention selects short-range ordered and long-range disordered microcrystalline graphite as the raw material of the porous graphite negative electrode, and its particles are formed by the accumulation of grains with a grain size of less than 1 μm. During the alkali activation process, the etching effect preferentially occurs on the end faces of the microcrystalline graphite flakes. During the activation process, the alkali acts as an etchant and etches along the end faces of different grains to the inside of the particles, while creating pores inward and ensuring the structural stability of the particles.
[0022] Furthermore, the particle size D of the microcrystalline graphite 50 1μm ~100μm.
[0023] In some specific embodiments, in step (1), the concentration of the alkaline solution is 16 wt% to 45 wt%.
[0024] In some specific embodiments, in step (1), the alkali contained in the alkali solution may include at least any one of potassium hydroxide, sodium hydroxide, etc., but is not limited thereto.
[0025] In some specific embodiments, in step (1), the mass ratio of the microcrystalline graphite to the alkaline solution is 1-100:100, that is, the mass content of the microcrystalline graphite in the alkaline solution is 1-100 wt %.
[0026] In some specific embodiments, in step (1), the temperature of the first calcination is 600°C to 1000°C, and the time of the first calcination is 6h to 20h.
[0027] In some specific embodiments, step (2) comprises: placing the first porous microcrystalline graphite obtained in step (1) in a reaction container, evacuating the container and letting it stand, then adding an alkaline solution, stirring evenly, and pressurizing the container to perform the vacuum pressure impregnation; the standing time is 5 min to 10 min.
[0028] Furthermore, step (2) further comprises: drying, washing to remove the alkali, and drying again after completing the vacuum pressure impregnation, and heating at a heating rate of 1 to 20 °C / min to perform the second calcination. In this step, washing away the alkali on the surface of the powder can effectively reduce the further etching of the particle surface and the collapse of the surface structure.
[0029] In some specific embodiments, in step (2), the process conditions adopted for vacuum pressure impregnation include: vacuum degree of 0.00001 Pa~100 Pa, and pressure of 1 MPa~50 MPa.
[0030] In some specific embodiments, in step (2), the temperature of the second calcination is 600°C to 1000°C, the time of the second calcination is 6h to 20h, and the second calcination is performed in an atmosphere formed by an inert gas.
[0031] Furthermore, in step (1) and step (2), the inert gas may include at least any one of nitrogen, argon, etc., but is not limited thereto.
[0032] In some specific embodiments, the concentration of the alkaline solution used in each repetition of the vacuum pressure impregnation of step (2) is 5-15% lower than that of the alkaline solution used in the previous operation, and the pressure used in each operation is 10-30% higher than that of the previous operation. The present invention repeatedly uses an alkaline solution to perform vacuum pressure impregnation on porous microcrystalline graphite, so that the alkali can enter the pore structure, further etch the inside of the particles at high temperature, and further promote the formation of the pore structure.
[0033] Furthermore, the preparation method specifically comprises: repeating the vacuum pressure impregnation and the second calcination in step (2) for multiple times until the porosity of the obtained porous microcrystalline graphite negative electrode material is 5-60%.
[0034] As one of the more specific embodiments, the method for preparing the porous microcrystalline graphite negative electrode material may include the following steps: (1) After the microcrystalline graphite is fully contacted with an alkaline solution, it is dried, and then a first calcination is performed in an inert atmosphere to obtain a first porous microcrystalline graphite with grain end faces etched; The specific preparation method of the first porous microcrystalline graphite is: mixing microcrystalline graphite powder and alkaline solution evenly, then drying, putting into an atmosphere furnace, introducing inert gas, heating to a certain temperature and performing a first calcination for a certain time to obtain the first porous microcrystalline graphite with grain end face etching; In step (1) of the present invention, the end faces of the surface grains of the microcrystalline graphite particles are etched to form irregular openings, wherein the size of the formed holes is between 10 nm and 1 μm, and the depth is between 500 nm and 3 μm.
[0035] In step (1) of the present invention, the temperature of the first calcination is 600°C to 1000°C, and the time of the first calcination is 6h to 20h.
[0036] In step (1) of the present invention, the reaction mechanism for preparing the first porous microcrystalline graphite is as follows: Reaction 1: Alkaline solution reacts with microcrystalline graphite at high temperature to etch 4MOH + C→M 2 CO 3 +M 2 O+2H 2 ↑, M is K or Na; Reaction 2: Potassium carbonate decomposes M at high temperature 2 CO 3 → M 2 O + CO 2 ↑; Reaction 3: Carbon dioxide reacts with microcrystalline graphite at high temperature to etch CO 2 + C→ 2CO↑.
[0037] (2) using an alkaline solution to perform vacuum pressure impregnation on the first porous microcrystalline graphite powder with etched grain end faces, specifically: evacuate the container containing the first porous microcrystalline graphite powder to 0.00001 Pa~100 Pa, let it stand for 5~10 minutes, then add 1~45% alkaline solution and stir evenly, pressurize to 1 MPa~50 MPa and then take it out; after drying, use deionized water to wash away the alkaline substances remaining on the surface, dry again, put it into an atmosphere furnace, pass nitrogen, heat to 600~1000℃, and perform a second calcination for 6~20 hours, so as to obtain a second porous microcrystalline graphite with further etching and simultaneous etching of the grain end faces and interior; In both steps (1) and (2) of the present invention, etching is performed along the gaps between the grains to form pores. However, compared with the first porous microcrystalline graphite obtained in step (1), the second porous microcrystalline graphite obtained in step (2) has a larger pore size on the outer surface, and has more pore structures inside the particles and penetrates deeper into the core of the particles.
[0038] (3) According to the particle size and the porosity of the desired porous microcrystalline graphite (5-60%), step S2 is repeated a certain number of times, each time the concentration of the alkaline solution is reduced by 5-15% and the pressure is increased by 10-30%, thereby obtaining a porous microcrystalline graphite negative electrode material.
[0039] The final pores of the preparation method of the present invention are etched along the grain boundaries inside the particles, and thus are evenly distributed inside the microcrystalline graphite particles; the size and depth of the pores are related to the etching concentration and the number of times.
[0040] As another aspect of the technical solution of the present invention, it also relates to a porous microcrystalline graphite negative electrode material prepared by the aforementioned method, wherein the porous microcrystalline graphite negative electrode material includes aggregates formed by the mutual accumulation of grains with small flake structures, and the porous structure is evenly distributed on the surface and inside of the porous microcrystalline graphite negative electrode material, the porous structure is mainly distributed along the edges of the grains, and the porous structure is located between the grains; wherein the average size of the grains with the small flake structure is below 1 μm, and the true density is 2~2.29 g / cc.
[0041] Furthermore, the porous microcrystalline graphite negative electrode material has a porosity of 5% to 60% and a specific surface area of 1 to 20 m 2 The porous microcrystalline graphite negative electrode material prepared by the preparation method of the present invention has a pore structure that is conducive to the rapid transmission of lithium ions and significantly improves the charge and discharge rate performance of the material.
[0042] Furthermore, the size of the porous microcrystalline graphite negative electrode material is 1-100 μm, and the degree of graphitization is 80-99%.
[0043] Furthermore, the average adsorption pore size of the porous microcrystalline graphite negative electrode material is 10-50 nm, and the average desorption pore size is 2-10 nm.
[0044] As another aspect of the technical solution of the present invention, it also relates to the application of the porous microcrystalline graphite negative electrode material in the preparation of lithium ion batteries.
[0045] Furthermore, another aspect of an embodiment of the present invention provides a lithium-ion battery, which includes the aforementioned porous microcrystalline graphite negative electrode material.
[0046] In summary, the present invention selects short-range ordered and long-range disordered microcrystalline graphite as the raw material of the porous graphite negative electrode. The etching action occurs preferentially on the end faces of the graphite flakes during the alkaline activation process. During the activation process, the etchant etches along the end faces of different grains toward the interior of the particles, creating pores inward while ensuring the structural stability of the particles.
[0047] In order to make the purpose, technical solution and application of the present invention clearer, the technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. The implementation conditions used in the following embodiments can be further adjusted according to actual needs, and the unspecified implementation conditions are usually the conditions in conventional experiments.
[0048] Example 1 (1) Mix 30wt% potassium hydroxide solution and D 50 =17µm microcrystalline graphite is mixed uniformly in a mass ratio of 1:0.5. After drying, nitrogen is introduced into an atmosphere furnace in a nitrogen atmosphere, and then the temperature is raised to 950℃ at a heating rate of 5℃ / min for the first calcination. The constant temperature is maintained for 7 hours, and then the temperature is naturally cooled. The morphology of the porous microcrystalline graphite is shown in the figure Figure 1 shown.
[0049] (2) The microcrystalline graphite with etched grain end faces obtained in step (1) is placed in a vacuum pressure impregnation device, and the vacuum degree is first drawn to 0.00001 Pa, followed by injection of a 35 wt% potassium hydroxide solution, and the pressure is increased to 10 MPa. After drying, the potassium hydroxide solution on the surface of the powder is rinsed off with deionized water, and nitrogen is introduced into an atmosphere furnace with a nitrogen atmosphere. The temperature is then increased to 900°C at a heating rate of 10°C / min for a second calcination, and the temperature is maintained at a constant temperature for 10 hours, followed by a natural cooling treatment to obtain porous microcrystalline graphite with the grain end faces and interior simultaneously etched.
[0050] (3) Repeat etching twice according to step (2), each time the potassium hydroxide concentration is reduced by 5 wt % and the pressure is increased by 10%, and finally a porous microcrystalline graphite negative electrode material is obtained. The morphology of the porous microcrystalline graphite negative electrode material finally obtained in this embodiment is shown in FIG. Figure 2As shown, it includes aggregates formed by the accumulation of small scale-structured grains, and the porous microcrystalline graphite negative electrode material has a porous structure evenly distributed on the surface and inside, the porous structure is mainly distributed along the edge of the grains, and the porous structure is located between the grains. The average size of the grains of the small scale-structure is less than 1 μm, the porosity of the porous microcrystalline graphite negative electrode material is 30%, and the specific surface area is 18m 2 / g, the size is 25-35 nm, and the 2C charging capacity retention rate is 40%.
[0051] Example 2 (1) Mix 20wt% potassium hydroxide solution and D 50 = 25µm microcrystalline graphite is evenly mixed in a mass ratio of 1:0.3. After drying, nitrogen is introduced into an atmosphere furnace with a nitrogen atmosphere, and then the temperature is increased to 850°C at a heating rate of 8°C / min for the first calcination, and the constant temperature is maintained for 10 hours, followed by natural cooling treatment.
[0052] (2) The microcrystalline graphite with etched grain end faces obtained in step (1) is placed in a vacuum pressure impregnation device, and the vacuum degree is first drawn to 0.0001 Pa, followed by injection of a potassium hydroxide solution with a concentration of 25 wt%, and the pressure is increased to 15 MPa. After drying, the potassium hydroxide solution on the surface of the powder is rinsed off with deionized water, and nitrogen is introduced into an atmosphere furnace with a nitrogen atmosphere. The temperature is then increased to 800°C at a heating rate of 8°C / min for a second calcination, and the temperature is maintained at a constant temperature for 20 hours, followed by a natural cooling treatment to obtain porous microcrystalline graphite with the grain end faces and the interior simultaneously etched.
[0053] (3) Repeat etching twice according to step (2), each time the potassium hydroxide concentration is reduced by 8 wt% and the pressure is increased by 15%, and finally a porous microcrystalline graphite negative electrode material is obtained with a porosity of 20% and a specific surface area of 15 m 2 / g, the size is 10-20nm, and the 2C charging capacity retention rate is 23%.
[0054] Example 3 (1) Mix 40wt% potassium hydroxide solution and D 50 =35µm microcrystalline graphite is mixed evenly in a mass ratio of 1:0.2. After drying, argon is introduced into an atmosphere furnace with an argon atmosphere, and then the temperature is increased to 750°C at a heating rate of 6°C / min for the first calcination, and the constant temperature is maintained for 15 hours, followed by natural cooling treatment.
[0055] (2) The microcrystalline graphite with etched grain end faces obtained in step (1) is placed in a vacuum pressure impregnation device, and the vacuum degree is first evacuated to 0.1 Pa, followed by injection of a 40 wt% potassium hydroxide solution, and the pressure is increased to 25 MPa. After drying, the potassium hydroxide solution on the surface of the powder is rinsed off with deionized water, and argon is introduced into an atmosphere furnace with an argon atmosphere. The temperature is then increased to 700°C at a heating rate of 6°C / min for a second calcination, and the temperature is maintained at a constant temperature for 12 hours, followed by a natural cooling treatment to obtain porous microcrystalline graphite with the grain end faces and interior simultaneously etched.
[0056] (3) Repeat etching three times according to step (2), each time the potassium hydroxide concentration is reduced by 10 wt% and the pressure is increased by 18%, and finally a porous microcrystalline graphite negative electrode material is obtained with a porosity of 35% and a specific surface area of 20 m 2 / g, the size is 40-50 nm, and the 2C charging capacity retention rate is 48%.
[0057] Example 4 (1) Mix 45wt% potassium hydroxide solution and D 50 =50µm microcrystalline graphite is mixed evenly in a mass ratio of 1:1. After drying, argon is introduced into an atmosphere furnace with an argon atmosphere. Then, the temperature is increased to 1000°C at a heating rate of 20°C / min for the first calcination, and the constant temperature is maintained for 6 hours, followed by a natural cooling treatment.
[0058] (2) The microcrystalline graphite with etched grain end faces obtained in step (1) is placed in a vacuum pressure impregnation device, and the vacuum degree is first drawn to 10 Pa, followed by injection of a 40 wt% potassium hydroxide solution, and the pressure is increased to 1 MPa. After drying, the potassium hydroxide solution on the surface of the powder is rinsed off with deionized water, and argon is introduced into an atmosphere furnace with an argon atmosphere. The temperature is then increased to 1000°C at a heating rate of 20°C / min for a second calcination, and the temperature is maintained constant for 6 hours, followed by a natural cooling treatment to obtain porous microcrystalline graphite with the grain end faces and interior simultaneously etched.
[0059] (3) Repeat etching twice according to step (2), each time the potassium hydroxide concentration is reduced by 15wt% and the pressure is increased by 20%, and finally a porous microcrystalline graphite negative electrode material is obtained with a porosity of 15% and a specific surface area of 10 m 2 / g, the size is 30-40 nm, and the 2C charging capacity retention rate is 18%.
[0060] Example 5 (1) Mix 16wt% sodium hydroxide solution and D 50=10µm microcrystalline graphite is mixed evenly in a mass ratio of 1:0.01. After drying, nitrogen is introduced into an atmosphere furnace with a nitrogen atmosphere, and then the temperature is increased to 600°C at a heating rate of 1°C / min for the first calcination, and the constant temperature is maintained for 20 hours, followed by a natural cooling treatment.
[0061] (2) The microcrystalline graphite with etched grain end faces obtained in step (1) is placed in a vacuum pressure impregnation device, and the vacuum degree is first evacuated to 100 Pa, and then a sodium hydroxide solution with a concentration of 30 wt% is injected, and the pressure is increased to 50 MPa. After drying, the sodium hydroxide solution on the surface of the powder is rinsed off with deionized water, and nitrogen is introduced into the atmosphere furnace with a nitrogen atmosphere. The temperature is then increased to 600°C at a heating rate of 1°C / min for a second calcination, and the constant temperature is maintained for 20 hours. The temperature is then naturally cooled to obtain porous microcrystalline graphite with the grain end faces and the interior simultaneously etched.
[0062] (3) Repeat etching three times according to step (2), each time the potassium hydroxide concentration is reduced by 5 wt% and the pressure is increased by 30%, and finally a porous microcrystalline graphite negative electrode material is obtained with a porosity of 45% and a specific surface area of 25 m 2 / g, the size is 20-30 nm, and the 2C charging capacity retention rate is 55%.
[0063] Comparative Example 1 This control example is basically the same as Example 1, except that steps (2) and (3) are not performed.
[0064] The obtained porous microcrystalline graphite negative electrode material has a porosity of 10% and is used in the preparation of lithium-ion batteries. The test results of the charge and discharge rate performance of the battery show that the 2C charging capacity retention rate is 12%.
[0065] Comparative Example 2 This control example is basically the same as Example 1, except that the concentration of the potassium hydroxide solution used in the vacuum pressure impregnation in step (3) is the same as that in step (2).
[0066] The morphology of the porous microcrystalline graphite negative electrode material is as follows: Figure 3 As shown, the results show that the internal pore structure is too large, the particle structure is unstable and easy to collapse, and the rate performance is poor. It is used in the preparation of lithium-ion batteries. The charge and discharge rate performance test results of the battery are: the 2C charging capacity retention rate is 30%.
[0067] Comparative Example 3 This control example is basically the same as Example 1, except that the vacuum degree used in the vacuum pressure impregnation in step (2) is too low.
[0068] The morphology of the porous microcrystalline graphite negative electrode material is as follows: Figure 4 As shown, the porosity is 15%, which is used in the preparation of lithium-ion batteries. The charge and discharge rate performance test results of the battery are: the 2C charge capacity retention rate is 19%. The reason may be that the vacuum is too low, and the alkaline solution cannot enter the deeper part of the etched hole in the previous step to etch further, so it cannot etch into the interior of the particle, resulting in low porosity of the particle, which is not conducive to performance improvement.
[0069] Comparative Example 4 This control example is basically the same as Example 1, except that the pressure used in the vacuum pressure impregnation in step (2) is too low. The reason may be that the pressure is too low, and the alkaline solution cannot enter the deeper part of the etched hole in the previous step, so it cannot etch into the inside of the particle, resulting in a low porosity of the particle, which is not conducive to performance improvement.
[0070] Comparative Example 5 Ordinary alkali fusion method is used. Ordinary alkali fusion method can only make pores on the surface of particles, but cannot continuously make pores inside particles, resulting in low porosity of powder and limited performance improvement.
[0071] The present invention can continuously generate pore structures inside microcrystalline graphite particles, making it easier for lithium ions to embed and escape, thereby greatly improving performance.
[0072] In addition, the inventors of this case also conducted experiments with other raw materials and conditions listed in this specification in accordance with the methods of Examples 1 to 5, and also produced porous microcrystalline graphite negative electrode materials with excellent charge and discharge rate performance.
[0073] It should be understood that the above are only specific application examples of the present invention and do not constitute any limitation on the protection scope of the present invention. Any technical solution formed by equivalent transformation or equivalent replacement falls within the protection scope of the present invention.
Claims
1. A method for preparing a porous microcrystalline graphite negative electrode material, characterized in that: include: (1) After the microcrystalline graphite is fully contacted with an alkaline solution, it is dried, and then a first calcination is performed in an inert atmosphere to obtain a first porous microcrystalline graphite with grain end faces etched; (2) vacuum pressure impregnating the first porous microcrystalline graphite obtained in step (1) with an alkaline solution, followed by drying, and then performing a second calcination in an inert atmosphere to obtain a second porous microcrystalline graphite with the end faces and the interior of the grains simultaneously etched; Repeat step (2) for more than one time, wherein the concentration of the alkaline solution used in each operation is 5-15% lower than that of the previous operation, and the pressure used in each operation is 10-30% higher than that of the previous operation, to obtain a porous microcrystalline graphite negative electrode material.
2. The preparation method according to claim 1, characterized in that Step (1) comprises: uniformly mixing microcrystalline graphite and an alkaline solution, drying the obtained mixture, introducing an inert gas, heating the mixture to a selected temperature at a heating rate of 1 to 20°C / min, and performing a first calcination to obtain a first porous microcrystalline graphite with grain end face etching; And / or, the size of the pores contained in the first porous microcrystalline graphite is 10 nm-1 μm, and the depth is 500 nm-3 μm.
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the microcrystalline graphite comprises microcrystalline graphite powder, the particles of which are formed by the accumulation of crystals with a grain size of less than 1 μm; and / or the particle size D of the microcrystalline graphite is 50 1μm ~100μm; and / or, in steps (1) and (2), the concentration of the alkaline solution is 16 wt% to 45 wt%; And / or, in steps (1) and (2), the alkali contained in the alkali solution includes at least one of potassium hydroxide and sodium hydroxide; And / or, in step (1), the mass ratio of the microcrystalline graphite to the alkaline solution is 1-100:
100.
4. The preparation method according to claim 2, characterized in that: In step (1), the temperature of the first calcination is 600°C to 1000°C, and the time of the first calcination is 6h to 20h; and / or the inert gas includes at least one of nitrogen and argon.
5. The preparation method according to claim 1, characterized in that Step (2) comprises: placing the first porous microcrystalline graphite obtained in step (1) in a reaction container, evacuating the container and letting it stand, then adding an alkaline solution, stirring evenly, and pressurizing the container to perform the vacuum pressure impregnation; the standing time is 5 min to 10 min; And / or, step (2) further comprises: after completing the vacuum pressure impregnation, drying, washing to remove the alkali, and drying again, and heating at a heating rate of 1-20°C / min to perform the second calcination.
6. The preparation method according to claim 1 or 5, characterized in that: In step (2), the process conditions adopted for vacuum pressure impregnation include: vacuum degree of 0.00001 Pa~100 Pa, and pressure of 1 MPa~50 MPa.
7. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the second calcination is 600°C to 1000°C, the time of the second calcination is 6h to 20h, and the second calcination is carried out in an atmosphere formed by an inert gas, wherein the inert gas includes at least one of nitrogen and argon.
8. The porous microcrystalline graphite negative electrode material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The porous microcrystalline graphite negative electrode material comprises an aggregate formed by the accumulation of grains with small scale structures, and the porous structure is evenly distributed on the surface and inside of the porous microcrystalline graphite negative electrode material, the porous structure is mainly distributed along the edge of the grains, and the porous structure is located between the grains; wherein the average size of the grains with small scale structures is less than 1 μm, and the true density is 2-2.29 g / cc; The porous microcrystalline graphite negative electrode material has a porosity of 5% to 60% and a specific surface area of 1 to 20 m 2 / g; The size of the porous microcrystalline graphite negative electrode material is 1-100 μm, and the degree of graphitization is 80-99%; The average adsorption pore size of the porous microcrystalline graphite negative electrode material is 10-50 nm, and the average desorption pore size is 2-10 nm.
9. Use of the porous microcrystalline graphite negative electrode material according to claim 8 in the preparation of lithium ion batteries.
10. A lithium ion battery, characterized in that: Includes the porous microcrystalline graphite negative electrode material as described in claim 8.
Citation Information
Patent Citations
Preparation method of porous hollow graphite material
CN106207180A
Porous carbon material, carbon-coated metal composite porous carbon material, preparation method thereof, negative plate and lithium ion battery
CN117525374A
Method of making porous graphene membranes and membranes made using this method
RU2827910C1
Cited By
Porous artificial graphite negative electrode material, preparation method thereof and application of porous artificial graphite negative electrode material in lithium ion battery
CN121107406A
Preparation method of anti-precipitation lithium graphite with amorphous carbon edge structure and application of anti-precipitation lithium graphite in field of lithium ion batteries
CN122144725A